Analysis of Water, Ash, and Crude Fiber Content in Jeruju Mangrove Leaf Tea (Acanthus ilicifolius L.) - Maria Marselina Ghela; sulfiana sulfiana; M Iksan Badarudin (Jurnal Perikanan dan Kelautan, 2026)
The mangrove plant Acanthus ilicifolius L. is a coastal species with considerable potential for development as a functional food, particularly in the form of herbal tea. This study aimed to evaluate the effect of oven-drying duration on the chemical characteristics of A. ilicifolius leaf tea, including moisture content, ash content, and crude fiber content. An experimental study was conducted using a Completely Randomized Design (CRD) with a single factor, namely oven-drying duration of 70, 85, and 100 minutes at 100°C, with three replications for each treatment. Data were analyzed using one-way analysis of variance (ANOVA), followed by Bonferroni's post hoc test at a 95% confidence level. The results showed that oven-drying duration significantly affected moisture content, ash content, and crude fiber content (p < 0.05). Moisture content decreased significantly from 13.38 ± 0.17% to 9.20 ± 0.16%, although it remained slightly above the maximum limit specified by the Indonesian National Standard (BSN, 2013; ≤8%). In contrast, ash content increased from 9.48 ± 0.16% to 11.73 ± 0.16%, exceeding the maximum SNI limit (8%). Crude fiber content exhibited a fluctuating pattern, measuring 12.14 ± 0.17% at 70 minutes, decreasing to 9.19 ± 0.18% at 85 minutes, and increasing to 12.73 ± 0.16% at 100 minutes; however, all treatments remained within the SNI requirement (≤16.5%). Bonferroni's post hoc test revealed significant differences among most treatment groups. These findings indicate that oven-drying duration significantly influences the chemical characteristics of A. ilicifolius leaf tea. Therefore, optimizing the drying duration is essential to produce a stable product that meets quality standards and is safe for consumption.